2014
DOI: 10.1210/jc.2013-3887
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sex Steroids With Bone Maturation, Bone Mineral Density, Bone Geometry, and Body Composition: A Cross-Sectional Study in Healthy Male Adolescents

Abstract: Circulating E2 is positively associated with bone maturation and aBMD and vBMD and negatively with endosteal circumference in healthy boys, whereas T is a determinant of lean mass and bone size. These findings underscore the important role of E2 in skeletal development in boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 34 publications
0
48
1
2
Order By: Relevance
“…During puberty, men develop larger bone size partly due to the interplay of sex steroids with mechanical loading (6,44), and positive relationships of testosterone with periosteal circumference have been observed in pubertal boys and young men (5,6,45). The current results cannot confirm the previously reported larger radial cortical bone size and thinner cortex in trans men after 10 year of testosterone treatment compared with control women (9), although the observation time was probably too short to detect changes.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…During puberty, men develop larger bone size partly due to the interplay of sex steroids with mechanical loading (6,44), and positive relationships of testosterone with periosteal circumference have been observed in pubertal boys and young men (5,6,45). The current results cannot confirm the previously reported larger radial cortical bone size and thinner cortex in trans men after 10 year of testosterone treatment compared with control women (9), although the observation time was probably too short to detect changes.…”
Section: Discussioncontrasting
confidence: 87%
“…Hence, quantitative computed tomography (QCT) and visualizing bone geometry can contribute for unraveling the interactions of sex steroid with trabecular and cortical bone. Sex steroids also influence bone size: men develop larger periosteal (outer) and endosteal (inner) circumference than women, partly due to the interplay of sex steroids, mechanical loading, and the growth hormone (GH)/ insulin-like growth factor 1 (IGF1)-axis during puberty (4,5,6). In adulthood, periosteal apposition continues, but at a slower rate in women than in men (7).…”
Section: Introductionmentioning
confidence: 99%
“…This explains why patients with aromatase deficiency resulting from inactivating mutation of the aromatase gene show undetectable levels of E 2 and, as a result, low BMD (9). Among male patients who are not aromatase deficient, aside from influencing bone maturation and peak bone mass acquisition, aromatase activity may also influence body composition, even at an early age (27,28). In a study among young males aged 6-19 years old, Vandewalle et al (27,28) reported that circulating E 2 was positively associated with skeletal maturation and areal and volumetric BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Among male patients who are not aromatase deficient, aside from influencing bone maturation and peak bone mass acquisition, aromatase activity may also influence body composition, even at an early age (27,28). In a study among young males aged 6-19 years old, Vandewalle et al (27,28) reported that circulating E 2 was positively associated with skeletal maturation and areal and volumetric BMD. In addition, lean mass in these patients was also found to positively correlate with higher testosterone levels (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation